Sequential Intravesical Gemcitabine and Docetaxel for bacillus Calmette-Guérin-Naïve High-Risk Nonmuscle-Invasive Bladder Cancer. Issue 3 (27th September 2022) - McElree, Ian M.; Steinberg, Ryan L.; Martin, Alex C.; Richards, Jordan; Mott, Sarah L.; Gellhaus, Paul T.; Nepple, Kenneth G.; O'Donnell, Michael A.; Packiam, Vignesh T.
Abstract : Abstract : Purpose: Bacillus Calmette-Guérin (BCG) is currently recommended as adjuvant therapy following complete transurethral resection of bladder tumor for high-risk nonmuscle-invasive bladder cancer (NMIBC). In response to the BCG shortage, gemcitabine plus docetaxel (Gem/Doce) has been utilized at our institution in the BCG-naïve setting. We report the outcomes of patients with high-risk BCG-naïve NMIBC treated with Gem/Doce. Materials and Methods: We retrospectively reviewed patients with BCG-naïve high-risk NMIBC treated with Gem/Doce from May 2013 through April 2021. Patients received 6 weekly intravesical instillations of sequential 1 gm gemcitabine and 37.5 mg docetaxel after complete transurethral resection of bladder tumor. Monthly maintenance of 2 years was initiated if disease-free at first followup. The primary outcome was recurrence-free survival. Survival was assessed with the Kaplan-Meier method, indexed from the first Gem/Doce instillation. Adverse events were reported using CTCAE (Common Terminology Criteria for Adverse Events) v5 (National Cancer Institute, Bethesda, Maryland). Differences were assessed with the log-rank test. Results: There were 107 patients with a median followup of 15 months included in the analysis. Patients had high-risk characteristics including 47 with any carcinoma in situ and 55 with T1 disease. Recurrence-free survival was 89%, 85% and 82% at 6, 12 and 24 months, respectively. Recurrence rates were similar between patients with or without carcinoma in situ (p=0.42). No patient had disease progression or died of bladder cancer. One patient underwent cystectomy due to end-stage lower urinary tract symptoms. Overall survival was 84% at 24 months. There were 92 adverse events (1 ≥grade 3), and 4 (4%) patients were unable to receive a full induction course. Conclusions: Gem/Doce is an effective and well-tolerated therapy for BCG-naïve NMIBC. Further investigation is warranted.